Exploring the effect of environmental sensitivity on emotional fluctuations among adolescents during the COVID-19 pandemic: a three-wave longitudinal study - Dragone, Mirella; Colella, Alessandra; Esposito, Concetta; Bacchini, Dario (Frontiers in Psychology, 2024)
Introduction The COVID-19 pandemic significantly impacted the emotional well-being of adolescents worldwide. Some studies suggested that individuals with high Environmental Sensitivity may have been more likely to experience poor psychological adjustment during the pandemic than those with lower sensitivity. However, there is still limited research on how emotional responses varied across different stages of the pandemic and whether Environmental Sensitivity increased adolescents’ vulnerability to the psychological impact of prolonged pandemic restrictions. Methods To address this gap, this study used a three-year longitudinal design (2020–2022) with a sample of 453 adolescents. They completed an online survey measuring their positive and negative emotions throughout the pandemic period, with Environmental Sensitivity considered a time-invariant covariate. Results The results revealed that all participants, regardless of their level of Environmental Sensitivity, experienced a decrease in positive emotionality between the first and second years. However, this trend reversed, showing an increase between the second and third years. Regarding negative emotions, highly sensitive adolescents experienced a significant linear increase over time. In contrast, low-and medium-sensitive adolescents exhibited a quadratic trend, with a notable increase in negative emotions between the first and second years, followed by a slight decrease between the second and third years. Discussion These findings provide further evidence of the negative impact of the pandemic on adolescents’ emotional well-being. They also support the notion that Environmental Sensitivity is associated with individuals’ ability to respond and adjust to adverse life events, with significant implications for future research and practice.